Honoring Curiosity - Glass, John (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Summary: Curiosity then, is something that does indeed need to be honored. It is anapproach to being with another that is often times overlooked when engaging in research.To be sure, it does occur within this context; however, when it occurs with the attached description in mind, with an appreciation of the depth of what curiosity has to offer the researcher, the outcome is decidedly different and decidedly more rewarding for all parties involved in